2007
DOI: 10.4049/jimmunol.178.5.2763
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Infiltrating Human Non-Small Cell Lung Cancer Are Blocked at Immature Stage

Abstract: Rapidly progressive dementia mimicking Creutzfeldt-Jakob disease (CJD) is a relatively rare presentation but a rewarding one to become familiar with, as the potential diagnoses range from the universally fatal to the completely reversible. Patients require urgent decisions about assessment and investigation and have quickly evolving needs for treatments and support, through symptom management and end-of-life care in most cases. We have based this pragmatic review on the experiences of a specialist prion referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
149
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(171 citation statements)
references
References 46 publications
16
149
0
1
Order By: Relevance
“…This is important, because relative to HPV-negative HNSCC, HPV + carcinomas associate with better prognosis [40,41], and we found that CD1a + DC infiltrate HPV + HNSCC in large numbers (manuscript in preparation). More recent studies revealed that tumor infiltrating DC contribute to immune escape due to their immature phenotype and low density of co-stimulatory molecules CD80 and CD86 [42,43]. Phagocytosis of tumor cells is known to contribute to a CCR7 + immature DC phenotype, and in our study, migrating DC showed evidence of phagocytosis of cytokeratin-positive cells (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…This is important, because relative to HPV-negative HNSCC, HPV + carcinomas associate with better prognosis [40,41], and we found that CD1a + DC infiltrate HPV + HNSCC in large numbers (manuscript in preparation). More recent studies revealed that tumor infiltrating DC contribute to immune escape due to their immature phenotype and low density of co-stimulatory molecules CD80 and CD86 [42,43]. Phagocytosis of tumor cells is known to contribute to a CCR7 + immature DC phenotype, and in our study, migrating DC showed evidence of phagocytosis of cytokeratin-positive cells (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…There is ample evidence that the function of DC subsets in spontaneous or transplanted tumours is dependent on maturation and activation status of DCs 4,35,36 . In Em-Myc transgenic mice that exhibit a large tumour mass, a decrease in the activating costimulatory molecule CD40, loss of MHC class II, and an increase in CD80 and PD-L1 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the subsets such as Treg participate in tumor-induced immune suppression. 25,26 Researchers proposed that adoptive cell transfer of TILs containing Tregs would greatly impair anti-tumor efficacy. 19 Therefore, Treg depletion from TILs should eliminate the negative regulation and optimize the effects of adoptive immunotherapy, especially in advanced tumor stage.…”
Section: Introductionmentioning
confidence: 99%